Juridical Review of Indonesian Banking Consumer Services (Commercial Banks and BPR) in the Digitalization Era - Clara Ignatia Tobing; Awaludin Marwan; Dinda Wardani; Elsa Febriana; Putri Cahyani Pasya; Raisah, Raisah revalinda alfianti; Rizky Khalid; Muhammad Uzaynullah; Yesi Putriani; Zeam Indra Gunawan (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2024)
The global banking sector is undergoing a significant transformation driven by disruptive technologies, particularly artificial intelligence. Banks worldwide, are embracing these technologies to reshape their future. By integrating AI, the banking sector can better understand human behaviour, improve automated processes, and reduce operational costs, enhancing customer retention, satisfaction, and overall performance. This adoption of AI is crucial for the sector's development and sustainability. The research is classified as normative juridical research, utilizing written materials as data sources. Qualitative research methods are employed to describe and analyze various phenomena and perspectives. The research relies on secondary data from library research, including official documents, research reports, and primary legal materials with authoritative significance. The legal framework governing the banking sector encompasses regulations issued by both Bank Indonesia (BI) and the Financial Services Authority (OJK), with the latest addition being the Financial Services Strengthening Law, specifically Law No. 4 of 2023, which includes provisions related to banks. The examination of consumer services banks provide is associated with compliance with the Consumer Protection Law, specifically Law No. 8 of 1999. Moreover, with the establishment of the Otoritas Jasa Keuangan (OJK), a comprehensive regulatory framework for digital banking in Indonesia, exemplified by Regulation Number 12/POJK.03/2018 has been made. This regulation highlights the increasing role of Information Technology in enhancing customer services, marking the banking sector's transition into the digital banking era. This transformation encompasses various customer interactions, from opening savings accounts to conducting financial transactions, driven by Information Technology's pervasive utilization.